EXPLORING POTENTIAL OF ALMOUR RAWA TOURISM OBJECT IN BONDOWOSO JAWA TIMUR - Nutyasih Wibawanti Ratna Amina; Teguh Priyo Sadono (Pringgitan, 2020)
This research aims to determine the potential of the Swamp of Indah Almour as a tourist attraction, when viewed from the aspect of economic benefits, aspects of the development of tourist destinations and the public's response to the development of the Swamp of Indah Almour tourism object as a sustainable tourist attraction in Bondowoso, East Java. The development and construction of Swamp of Indah Almour tourism object that leads to a comprehensive and comprehensive ecotourism, will become an economic resource for the local government and the local community. With a fairly high level of public awareness about tourist destinations, this has the greatest potential for the development of ecotourism which is currently more popular with tourists, and can maintain tourism sustainability. However, there are some things that still need to be addressed, including the need for more modern management of tourist sites and follow the current trends to attract more investors and tourists to visit. In addition, it is also necessary to improve the quality of human resources in managing tourist destinations in providing services and management of tourism objects.Keywords: indah almour swamp, sustainable tourism, economic benefits, people